Endothelial NOX4 Oxidase Negatively Regulates Inflammation and Improves Morbidity During Influenza A Virus Lung Infection in Mice - Hendricks, Keshia S.; To, Eunice E.; Luong, Raymond; Liong, Felicia; Erlich, Jonathan R.; Shah, Ajay M.; Liong, Stella; O’Leary, John J.; Brooks, Doug A.; Vlahos, Ross; Selemidis, Stavros (Frontiers in Cellular and Infection Microbiology, 2022)
Endosomal NOX2 oxidase-dependent ROS production promotes influenza pathogenicity, but the role of NOX4 oxidase, which is highly expressed in the lung endothelium, is largely unknown. The aim of this study was to determine if endothelial NOX4 expression can influence viral pathology in vivo, using a mouse model of influenza infection. WT and transgenic endothelial NOX4 overexpressing mice (NOX4 TG) were infected intranasally with the Hong Kong H3N2 X-31 influenza A virus (104 PFU; HK x-31) or PBS control. Mice were culled at either 3 or 7 days post-infection to analyse: airway inflammation by bronchoalveolar lavage fluid (BALF) cell counts; NOX4, as well as inflammatory cytokine and chemokine gene expression by QPCR; and ROS production by an L-012-enhanced chemiluminescence assay. Influenza A virus infection of WT mice resulted in a significant reduction in lung NOX4 mRNA at day 3, which persisted until day 7, when compared to uninfected mice. Influenza A virus infection of NOX4 TG mice resulted in significantly less weight loss than that of WT mice at 3-days post infection. Viral titres were decreased in infected NOX4 TG mice compared to the infected WT mice, at both 3- and 7-days post infection and there was significantly less lung alveolitis, peri-bronchial inflammation and neutrophil infiltration. The oxidative burst from BALF inflammatory cells extracted from infected NOX4 TG mice was significantly less than that in the WT mice. Expression of macrophage and neutrophil chemoattractants CXCL10, CCL3, CXCL1 and CXCL2 in the lung tissue were significantly lower in NOX4 TG mice compared to the WT mice at 3-days post infection. We conclude that endothelial NOX4 oxidase is protective against influenza morbidity and is a potential target for limiting influenza A virus-induced lung inflammation.